Moderation of non-performing financing on the effect of buying and selling financing on return on assets empirical study on Islamic banking in Indonesia in 2015-2020 - Jajuli Jajuli; Imam Sofi'i; Didit Haryadi (International Journal of Applied Finance and Business Studies, 2023)
Banking is an institution that has an essential role in driving the economy. This research aims to develop a research model to overcome business phenomena and the research gap between buying and selling financing and the Return on Assets ratio with the non-performing financing ratio as a moderating variable. The method used by the author in this research is a quantitative descriptive method with an associative approach. The population in this study was 13 Islamic banks listed on the Indonesia Stock Exchange. The sample in this research is 9 Islamic banking companies according to research variables regarding public financial reports for 2015-2020. The sampling technique using purposive sampling was used. Data analysis techniques using regression and path analysis use the moderating regression analysis test. The research results show that buying and selling financing significantly affects Return On Assets, non-performing funding significantly impacts return on assets, and non-performing financing can moderate and strengthen the influence of buying and financing of sale on return on assets. The author hopes this research can provide a theoretical contribution to this context's financial management and banking literature.